MANFAAT PROMOTIF DAN PREVENTIF BPJS SEBAGAI PEMENUHAN HAK KESEHATAN BAGI SISWA SEKOLAH DASAR - Yesi Anita; Rafhi Febryan Putera; Hasmai Bungsu Ladiva (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe the promotive and preventive benefits of the BPJS program for the health maintenance of elementary school students in the working area of Belimbing Puskesmas. This type of research is qualitative descriptive with data validity test with ktriangulasi technique and data analysis technique using interactive analysis model from Miles and Huberman. The findings of this study indicate that the promotive benefits of health promotion are done by displaying banners, pamphlets, stickers and leaflets. Information provided such as TB alert, dengue alert, and the dangers of smoking. Preventive benefits are undertaken in an attempt to prevent, avoid or reduce the risk of adverse outcomes of the disease, through immunization and diphtheria injections for all primary school children. Keywords: Promotive, Preventive, Rights, Health